2019
DOI: 10.1080/09540121.2019.1653436
|View full text |Cite
|
Sign up to set email alerts
|

Association of HIV status with sexual function in women aged 45–60 in England: results from two national surveys

Abstract: Increasing numbers of women living with HIV are reaching their midlife. We explore the association of HIV status with sexual function (SF) in women aged 45-60 using two national cross-sectional surveys: the third British National Survey of Sexual Attitudes and Lifestyles ("Natsal-3") and "PRIME", a survey of women living with HIV attending HIV clinics across England. Both studies asked the same questions about SF that take account not only sexual difficulties but also the relationship context and overall level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…For each symptom, perceived severity was scored on a Likert-type scale from 0 ( symptoms not present ) to 4 ( very severe ). A composite score was calculated by summing the scores and was categorized as: no/few (0–4), mild , 5 8 moderate 9 16 and severe (⩾ 17) symptoms. 19 …”
Section: Methodsmentioning
confidence: 99%
“…For each symptom, perceived severity was scored on a Likert-type scale from 0 ( symptoms not present ) to 4 ( very severe ). A composite score was calculated by summing the scores and was categorized as: no/few (0–4), mild , 5 8 moderate 9 16 and severe (⩾ 17) symptoms. 19 …”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown the negative impact of menopause on sexual functioning among healthy women, with impairment of their quality of life 15,16 . As expected, low sexual function (LSF) is more common in postmenopausal compared to premenopausal women living with HIV 7 . This situation is even worse since an increased probability of premature menopause 17 and more severe menopausal symptoms has been observed in HIV-infected women 18,19 .…”
mentioning
confidence: 91%
“…Therefore, as part of the comprehensive evaluation of HIV, the sexuality arena requires special attention. Even though the prevalence of sexual problems is higher in HIV-infected women than in noninfected ones, 6,7 the literature is still limited. Unfortunately, a meta-synthesis revealed that living with HIV was a burden for women in sexuality and reproduction 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both HIV and menopause are associated with an increased risk of comorbidities, particularly osteoporosis, insulin resistance [2][3][4] and cardiovascular disease [5][6][7] and are associated with increased rates of mental ill health compared with HIVnegative, non-menopausal women [8][9][10]. In addition, recently published data report lower overall sexual function in HIV-positive women accessing care in England compared with HIV-negative women [11]. The apparent effects of menopause on physical and mental health led to the publication of the British Menopause Society (BMS) vision statement for menopause care in the UK, which recommends delivery of integrated care based on the needs of the individual [12].…”
Section: Introductionmentioning
confidence: 99%